2020
DOI: 10.21203/rs.2.22105/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome analysis reveals the GRAS family in Salvia miltiorrhiza hairy roots in response to gibberellin

Abstract: Background: Salvia miltiorrhiza is one of the most important traditional Chinese medicinal plants with high medicinal value. Gibberellins are growth-promoting phytohormones that regulate numerous growth and developmental processes. However, their role in regulating secondary metabolism has not been investigated. Results: In this study, we found that GA can promote hairy roots growth and increase the content of tanshinones and phenolic acids. Transcriptome sequencing revealed that secondary metabolism pathway g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The pathway of secondary metabolite biosynthesis can be explained by the identification of candidate genes and important regulatory factors. The best inducer for screening the Astragalus polysaccharide metabolic pathway is silver nitrate solution, the best treatment site is the underground part, the best treatment time is 6-9 days, and the best polysaccharide content change detection site is the Astragalus root; 36 unigenes were found in the metabolic pathway of the polysaccharides metabolized [46]. Studies have found that methyl jasmonate, salicylic acid, IAA, and NAA promote the accumulation of Astragalus hairy root polysaccharides and total saponins, and IBA and 2.4-D have a negative effect on the accumulation of Astragalus hairy root polysaccharides and total saponins [47].…”
Section: Astragalus Polysaccharidementioning
confidence: 99%
“…The pathway of secondary metabolite biosynthesis can be explained by the identification of candidate genes and important regulatory factors. The best inducer for screening the Astragalus polysaccharide metabolic pathway is silver nitrate solution, the best treatment site is the underground part, the best treatment time is 6-9 days, and the best polysaccharide content change detection site is the Astragalus root; 36 unigenes were found in the metabolic pathway of the polysaccharides metabolized [46]. Studies have found that methyl jasmonate, salicylic acid, IAA, and NAA promote the accumulation of Astragalus hairy root polysaccharides and total saponins, and IBA and 2.4-D have a negative effect on the accumulation of Astragalus hairy root polysaccharides and total saponins [47].…”
Section: Astragalus Polysaccharidementioning
confidence: 99%